Assessment of the minimal available phosphorus needs of pullets during the pre-laying period. (25th October 2017) - Jing, M; Zhao, S; Rogiewicz, A; Slominski, B A; House, J D
Abstract: Dietary phosphorus (P) oversupply is costly to the poultry industry and represents a point source of excessive P discharge to the environment via manure application to soils. The current study was conducted to investigate the effects of dietary available P (AP) level on growth performance, plasma biochemistry, bone characteristics, and P flow in order to assess minimal AP needs of pullets during the pre-lay period. A total of 192 Lohmann pullet chicks were randomly allocated to one of 4 treatments with 8 replicate cages of 6 birds per cage. The pullets of Low (L; the lowest AP regimen) were fed diets in a sequence of 0.200, 0.175, and 0.150% AP for the age period of 0 to 4 wk, 4 to 8 wk, and 8 to 16 wk, respectively. The AP level was increased by an increment of 0.1% in each phase in Low-Medium (LM), Medium-High (MH) and High (H), thus making H (control) consisting of 0.500, 0.475, and 0.450% AP. Overall, there were no main effects of treatment on body weight gain (BWG), feed intake (FI) and feed conversion ratio (FCR). However, compared with the H treatment, BWG or FI of the L treatment was lower during the first 8 wk post-hatch, but became comparable or higher over the last 8 wk ( P < 0.05); FCR of L birds was greater over wk 0 to 4 but became smaller over wk 8 to 16 ( P < 0.05). Plasma P was lower in L than H treatments at wk 8 but turned comparable at wk 16 ( P < 0.001). Bone characteristics were not different for pullets fed various AP regimens. Total P intake and excretion were reduced with lowering dietary AP ( P < 0.001), but its retention percent was not affected. The results indicated that the lowest AP regimen (0.200–0.175–0.150%) in the current study was adequate to support healthy growth and development of pre-lay pullets, while reducing P excretion in manure.